Effects of climate on the phenology of Annona senegalensis Pers. (Annonaceae) and the distribution of associated insects in Burkina Faso - Zézouma Anselme Dao; Rahim Romba; Bruno Jaloux; Amadé Ouedraogo; Olivier Gnankine (Ecology and Evolution, 2024)
Abstract Climate change and global warming in the Sahelian region cause dramatic drought and advancing of the desert. This phenomenon could affect the plant survival and community composition, but even for surviving plants, it could affect their phenology and the insect community associated with them. In a space‐for‐time approach, we studied the case of Annona senegalensis Pers. (Annonaceae), a common shrub in tropical areas, to determine the impact of climate change on its phenology and the insects associated with its flowers and fruits. We determined the phenology phases of Annona senegalensis during a 1‐year period and assessed the abundance and diversity of insects in the Sudanian and the Sudano‐Sahelian climatic zones of Burkina Faso. Temperature, rainfall and relative humidity were recorded during 12 months in two sites per zone. Leafing of Annona senegalensis lasted 10 months in the Sudanian zone, flowering and fruiting were 3 months long. In the Sudano‐Sahelian zone, leafing lasted 8 months while flowering and fruiting were 3 and 4 months long, respectively. A total of 10,040 insects belonging to 48 species were collected in the two climatic zones. Forty‐six species were found in the Sudanian zone while 25 species were recorded in the Sudano‐Sahelian one. The variations in the plant phenology and the insect community were mainly due to the variation in rainfall across both climatic zones. Our results emphasize that advancing of the desert due to climate change could not only affect the survival of plants but for resistant species it also affect their interactions with insects and the whole insect community associated.